Topical Astodrimer Sodium, a Non-Toxic Polyanionic Dendrimer, Demonstrates Antiviral Activity in an Experimental Ocular Adenovirus Infection Model - Romanowski, Eric G. (Molecules, 2021)
There is no approved antiviral therapy for adenovirus (HAdV) ocular infections. Astodrimer sodium (SPL7013) is a polyanionic dendrimer with antiviral activity. The current study evaluated the ocular tolerability and anti-adenoviral efficacy of topical SPL7013 in rabbit ocular models. In a tolerability study, rabbits were treated with 3% SPL7013, vehicle, or 0.5% cidofovir. Their eyes were graded using the Draize scale. In antiviral efficacy studies, HAdV5 inoculated eyes were treated with 3% SPL7013, vehicle, or 0.5% cidofovir. Eyes were cultured for the virus on days 0, 1, 3, 4, 5, 7, 9, 11, and 14. Viral titers were determined. There were no differences in Draize scores between 3% SPL7013 and vehicle on any day. Cidofovir produced significantly higher Draize scores on day 12 than SPL7013 and vehicle. The 3% SPL7013 and 0.5% cidofovir significantly reduced daily viral titers and positive cultures per total compared with vehicle on several different days. The 3% SPL7013 and 0.5% cidofovir significantly reduced the duration of HAdV5 shedding compared to vehicle. The 3% SPL7013 demonstrated significantly more antiviral activity compared with vehicle in the Ad5/NZW rabbit ocular model. The 3% SPL7013 induced “minimal” to “practically non-irritating” Draize scores in the ocular tolerability study. Further development of astodrimer sodium as a topical antiviral therapy for adenoviral ocular infections is indicated.